FANCF hypomethylation is associated with colorectal cancer in Han Chinese - Hang Yu; Ranran Pan; Tong Gao; Dongping Wu; Jieer Ying; Shiwei Duan (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Fanconi anemia complement group F (FANCF) is known to be involved in DNA repair, and the overexpression of FANCF protein leads to cell proliferation and ultimately to cancer. The purpose of this study was to assess whether FANCF methylation was associated with colorectal cancer (CRC). Materials and Methods: A case-control experiment was conducted to study the association between FANCF methylation and CRC. We used quantitative methylation-specific PCR to measure the FANCF promoter methylation, and the percentage of methylation reference (PMR) to quantify the FANCF promoter methylation level. To investigate the effect of the selected FANCF fragment on gene expression regulation, we also performed a dual-luciferase reporter gene assay. Results: The results indicated that FANCF methylation in CRC tumor tissues was significantly lower than that in the nontumor tissues (median PMR: 44.86% vs. 65.77%, p=0.00001). Analysis of receiver-operating characteristic curves showed that FANCF hypomethylation had a diagnostic value for CRC (area under curve [AUC]: 0.670, sensitivity: 55.8%, specificity: 71.7%, p=0.00001). The dual-luciferase reporter assay showed that the FANCF fragment upregulated gene expression (fold change: 1.93, p=0.002). Conclusion: Research demonstrates for the first time that FANCF hypomethylation is significantly associated with CRC risk. FANCF hypomethylation may ultimately increase the risk of CRC by upregulating the expression of FANCF. Cite this article as: Yu H, Pan R, Gao T, Wu D, Ying J, Duan S. FANCF hypomethylation is associated with colorectal cancer in Han Chinese. Turk J Gastroenterol 2020; 31(8): 558-65.